How the Grinch stole Christmas - Seuss, Dr.; Jones, Chuck, 1912-2002.; Karloff, Boris, 1887-1969.; MGM/UA Home Video (Firm) (New York : MGM/UA Home Video, 1988)
The Grinch decides that he can't take anymore happiness from the Who village, so he and his dog Max steal everything from trees and ornaments down to the last can of Who hash. They find that Christmas is more than presents, however.
Animated.
Originally released as a motion picture in 1966.
Narrated by Boris Karloff ; music, Albert Hague.
Not rated.
General.
VHS Hi-fi.
Keywords: Animated films; Children's films; Christmas stories; Video recordings for the hearing impaired; Christmas films